A probability tomography approach to the analysis of potential field data in the Campi Flegrei caldera (Italy) - D. Patella; T. Iuliano; P. Mauriello (Annals of Geophysics, 2001)
The results of the application of the 3D probability tomography imaging approach to the study of the Campi Flegrei (CF) caldera are presented and discussed. The tomography approach has been applied to gravity, magnetic and ground deformation data already available in literature. The analysis of the 3D tomographic images is preceded by a brief qualitative interpretation of the original survey maps and by an outline of the probability tomography approach for each geophysical prospecting method. The results derived from the 3D tomographic images are the high occurrence probabilities of both gravity and ground deformation source centres in the CF caldera under the town of Pozzuoli. A Bouguer negative anomaly source centre is highlighted in the depth range 1.6-2 km b.s.l., whereas a positive ground deformation point source, responsible for the bradyseismic crisis of 1982-1984, is estimated at a mean depth of 3-4 km b.s.l. These inferences, combined with the results of a previous analysis of magnetotelluric, dipolar geoelectrical and self-potential data, corroborate the hypothesis that the bradyseismic events in the CF area may be explained by hot fluids vertical advection and subsequent lateral diffusion within a trapped reservoir overlying a magma chamber.